2011
DOI: 10.1176/appi.ps.62.9.1098
|View full text |Cite
|
Sign up to set email alerts
|

Medical Comorbidity and Functional Status Among Adults With Major Mental Illness Newly Admitted to Nursing Homes

Abstract: Objective This study compared comorbid conditions and functional status among elderly and nonelderly individuals with mental illness who were newly admitted to nursing homes. Methods Data were drawn from the Centers for Medicare & Medicaid Services national registry of nursing home residents from the Minimum Data Set in 2008. Results Among newly admitted individuals with schizophrenia, those younger than 65 accounted for a majority (60.3%) of admissions and had lower rates of medical illnesses and were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Findings from this study revealed that caregivers experience an array of burdens, which include physical, emotional impact, and psychological strain. This supports the finding of Aschbrenner et al (2011) who observed in their study that caregivers experienced burdens, which are conceptualized as the range of negative emotional reactions to caregiving. Vitaliano et al (2003) also documented that caring for a family member with dementia is generally regarded as a chronically stressful process, with potentially negative physical health consequences.…”
Section: Discussionsupporting
confidence: 88%
“…Findings from this study revealed that caregivers experience an array of burdens, which include physical, emotional impact, and psychological strain. This supports the finding of Aschbrenner et al (2011) who observed in their study that caregivers experienced burdens, which are conceptualized as the range of negative emotional reactions to caregiving. Vitaliano et al (2003) also documented that caring for a family member with dementia is generally regarded as a chronically stressful process, with potentially negative physical health consequences.…”
Section: Discussionsupporting
confidence: 88%
“…Findings from this study revealed that caregivers experienced a severe degree of burden. This supports the finding of Aschbrenner, Cai who observed in their study that caregivers experienced burden, which is conceptualised as the range of negative emotional reactions to caregiving. Vitaliano, Young , Vitaliano, Zhang also submitted that caring for a family member with dementia is regarded as a chronically stressful process, with potentially negative physical health consequences.…”
Section: Discussionsupporting
confidence: 89%
“…In an earlier study, 25% of very-late-onset patients with functional psychoses, including schizophrenia and related disorders, were institutionalized within ten years of index admission (Holden, 1987). Patients with schizophrenia have been reported to start living in institutional care at younger age than adults with mental problems other than schizophrenia or general population and they sometimes even lack a clear indication for admittance (Aschbrenner et al, 2009). Median age on admission to residential care was 65 years for patients with schizophrenia and 80 years for individuals with no mental illness (Andrews et al, 2009).…”
Section: Discussionmentioning
confidence: 99%